Strong interaction of single-atom Pt with Cd0.5Zn0.5S: electronic structure regulation and photocatalytic hydrogen evolution promotion. (March 2023) - Li, B.; Guo, C.; Wang, X.; Dong, W.; Xu, B.; Xing, X.; Zhou, D.; Xue, X.; Luan, Q.; Tang, W.; Hou, C.
Abstract: Rationally designing coordination configuration of single-atom co-catalyst to boost charge separation and enhance reaction kinetics is a significant challenge. Here, a single Pt atom lattice-doped PtSA -Cd0.5 Zn0.5 S photocatalyst with stable Pt-S3 configuration was successfully prepared through a facile solvothermal combined with ion substitution reaction method. In particular, the crucial role of Pt single atoms in charge separation and transmission is illustrated via identifying the dynamic configurational evolution of Pt species during the catalytic process. The strong d-p orbitals hybridization of Pt-S coordination bond endows remarkable stability of lattice-doped Pt sites and simultaneously triggers the catalytic activity of S sites by regulating the surface electronic structure, increased active sites for hydrogen evolution. As a result, the lattice-doped Pt single atom proceeds efficient photocatalytic hydrogen evolution activity of PtSA -Cd0.5 Zn0.5 S via regulated band structure, improved charge separation, and reduced hydrogen evolution energy barrier. The PtSA -Cd0.5 Zn0.5 S exhibits an enhanced photocatalytic hydrogen evolution activity of 279.11 μmol·h −1, which is 84 and 3.7 times of Cd0.5 Zn0.5 S (3.31 μmol·h −1 ) and PtSA /Cd0.5 Zn0.5 S (Pt single atom surface modification, 75.34 μmol·h −1 ), respectively. Highlights: Atomically dispersed Pt sites are immobilized into the lattice of PtSA -Cd0.5 Zn0.5 S photocatalyst through a facile solvothermal combined with ion substitution reaction strategy. The lattice-doped Pt single atom dramatically improved photocatalytic H2 evolution activity of PtSA -Cd0.5 Zn0.5 S via regulated band structure, improved charge separation, reduced hydrogen evolution energy barrier and activated S sites, about 84-fold higher than that of pristine Cd0.5 Zn0.5 S. The strong electron interaction of Pt with S prevents the aggregation of Pt single atom after long-term evolution of H2, endowing the PtSA -Cd0.5 Zn0.5 S with excellent catalytic stability.